Understanding Mobile Application Usage During the 2014 FIFA World Cup - Domingues, Augusto C. S. A.; Silva, Fabrício A.; Silva, Thais Regina M. Braga; Diniz, Luis G. A. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
Understanding how users consume mobile services during large events is a key factor in the improvement of the provided services. In 2014, Brazil hosted the FIFA World Cup, one of the biggest events in the world. The objective of this work is to exploit mobile data to discover important insights on how Brazilians accessed mobile applications during this event. The dataset studied here is composed of mobile application usage records collected during 2014 by a software agent installed on smartphones of 5,342 Brazilians. The results reveal interesting findings regarding how mobile accesses differ during the matches in comparison with ordinary days.